CRYSTALS BANDS ON THE SURFACE OF FRESHWATER ULVA TAXA - Messyasz, Beata; Rybak, Andrzej; Pikosz, Marta (My University, 2013)
The incrustation process is an important occurrence whose effects were noticeable in the changes in growth of species from genera Ulva. It consisted in the precipitation of calcium carbonate on the surface of the cells wall of the freshwater macrogreen alga. The calcium carbonate occurred abundantly and formed characteristic bands on the surface of Ulva thalli. Surface incrustation of calcite was clearly rugged. In the first phase of development Ulva thalli growth naturally, could reach up to 1 m and was thin and smooth to the touch. It was correlation with small numbers of crystals on the surface. But with time, thalli becomes shorter and rough. The mass of deposit crystals increased with the age of Ulva thalli, which may constitute up to half of the dry weight of algae. The great density range of crystals was natural for mature thalli. The main aim of this study was to determine the morphology of the calcium carbonate crystals from the surface of freshwater Ulva taxa.
Messyasz B., Rybak A., Pikosz M. (2011). Culture crystals bands on the surface of freshwater Ulva taxa. II Konferencja Naukowo – Dydaktyczna Wydziału Biologii Uniwersytetu im. Adama Mickiewicza w Poznaniu. Challenges for Contemporary Biology, Biotechnology and Environmental Protection, Poznań – Morasko, 5-7 kwiecień 2011, ISBN 978-83-88572-99-9, pp. 112-113 (POSTER).
Keywords: Incrustation; Freshwater Ulva; CaCO3